Genome-resolved characterization of candidate thermotolerance traits and predicted protein conformational behavior in Calditerricola during hyperthermophilic composting of organic wastes - Xu Li; Zhengnan Zhu; Youzhao Wang; Yanping Zhang; Xiaoyan Dang; Chaoyue Zhao; Shujie Hou; Bingzhen Li; Feng Ma; Liying Hao; Tong Zhu (Bioresource Technology, 2026)

Non-equilibrium phase change during CO2 depressurization: a comprehensive review of thermodynamics, experiments, modeling, and safety implications for high-pressure CO2 pipeline rupture - Qifan Wang; Gengyuan Tian; Le Ma; Yanping Huang (Annals of Nuclear Energy, 2026)

Evolution of fine structure and pasting properties in wheat starch during medium-high-temperature Daqu fermentation - Zhenbing Ma; Yuanyuan Tian; Dong Zhao; Lihua Zhao; Jia Zheng; Jian Su; Yanping Lu; Yi Ma (Food Research International, 2026)

Pre-lithiation strategy enhancing interfacial stability of carbon-coated SiO anodes via controlled formation of LixSiyOz for high-energy lithium-ion batteries - Hong Dong; Yanping Ma; Xiaobin Zhou; Jinying Hou; Juan Xin; Mingzhu Wei; Jianyao Zhu; Shiyou Li; Ya-Jun Cheng (Chemical Engineering Journal, 2026)

Sustained activation of peracetic acid by hydroxylamine and ferrous irons for enhanced short-chain fatty acids production from sludge fermentation - Guilin Ma; Yanping Zhang; Jing Zhang; Kun Yang; Shuyu Yang (Journal of Water Process Engineering, 2026)

Molecular dynamics evidence for bidirectional feedback between PFAS and humic acid during composting: Interaction mechanisms, conformational reorganization, and diffusion regulation - Shujie Hou; Chaoyue Zhao; Xu Li; Yanping Zhang; Bingzhen Li; Ziwei Dai; Qiyu Gong; Xinchang Zhou; Xiaolong Gao; Feng Ma; Yaonan Zhu; Fuxin Yang; et al. (Journal of Hazardous Materials, 2026)

Early thermal pulses drive interfacial pre-aging and plastisphere pre-shaping: An overlooked pre-conditioning pathway in PLA microplastic aging during composting - Yanping Zhang; Youzhao Wang; Chaoyue Zhao; Fuxin Yang; Xu Li; Shujie Hou; Bingzhen Li; Zhengnan Zhu; Ziwei Dai; Ziqian Wang; Xinchang Zhou; Qiyu Gong; et al. (Journal of Hazardous Materials, 2026)

Phage therapy: A novel strategy to combat drug-resistant Salmonella Pullorum infection in chickens - Hongzhe Zhao; Shilong You; Jiahao Fu; Xiaoyu Xiong; Yingying Ma; Xiaona Wang; Rongyan Li; Fei Teng; Mingze Chen; Wei Wu; Guiwei Li; Yanping Jiang; et al. (Veterinary Microbiology, 2026)

RAD23A promotes multiple myeloma cell survival through DNA damage response, proteostasis and enhanced metabolic activity - Hongxiu Liu; Yihua Wang; Xunru Liu; Ni Yang; Senxin Wang; Jie Zhao; Yaqi Shi; Huichao Wang; Yanping Ma (Toxicology and Applied Pharmacology, 2026)

Ethylene responsive transcription factors alleviate browning in fresh in-hull walnut (Juglans regia. L) by modulating GABA metabolism under controlled atmosphere storage - Niu Ye; Guoli Dai; Shizhe Liu; Yongqi Zhang; Shan Liu; Sike Wang; Yuwei Wang; Yuanlin Gou; Ting Zhang; Yanping Ma; Qinggang Zhu; Huiling Ma (Postharvest Biology and Technology, 2026)

Corrigendum to “Thermally driven polymer disentanglement: An overlooked Key pathway in PBAT-microplastic aging during composting” [J Hazard Mater 503 (2026) 141080] - Yanping Zhang; Xu Li; Youzhao Wang; Fuxin Yang; Chaoyue Zhao; Shujie Hou; Bingzhen Li; Ziwei Dai; Yang Yun; Feng Ma; Liying Hao; Tong Zhu (Journal of Hazardous Materials, 2026)

Molecular mechanism by which high temperature and RecBCD synergistically lower strand-separation barriers and promote destabilization of representative efflux-pump ARG fragments (macB/tetA) during hyperthermophilic composting - Xu Li; Youzhao Wang; Xiaoyan Dang; Yanping Zhang; Chaoyue Zhao; Shujie Hou; Bingzhen Li; Feng Ma; Liying Hao; Tong Zhu (Journal of Hazardous Materials, 2026)

Uncovering time-lagged causal mechanisms in hyperthermophilic composting using Peter–Clark momentary conditional independence algorithm - Yanping Zhang; Youzhao Wang; Ling Zhou; Fuxin Yang; Xu Li; Chaoyue Zhao; Shujie Hou; Bingzhen Li; Ziwei Dai; Ziqian Wang; Xinchang Zhou; Qiyu Gong; et al. (Bioresource Technology, 2026)

Characteristics of soil organic carbon and its stability under different vegetation types and restoration years in Hongze lake wetland, China - Yanan Bai; Haikun Wu; Huifeng Lu; Yuling Yang; Yanping Wang; Lei Dai; Yuchun Ma; Jinqi Wang; Yuzhi Song; Lidong Shen (Journal of Environmental Management, 2026)

Genetic Basis of α-1,3 Galactose Epitopes in Animal Reservoirs of Coronaviruses - Xinjia Mai; Chenxi Zhu; Yu He; Nian Wang; Yue Ma; Wen Zhang; Yanping Wang; Yunsen Li; Dapeng Zhou (Phenomics, 2026)

Water temperature affects pathogenicity of ranavirus to adult bullfrogs - Yanping Ma; Le Hao; Xi Liang; Gang Wang; Zhenxing Liu (Aquaculture, 2026)

Overcoming gastrointestinal mucosal barriers: Mechanistic innovations and technical advances in mucosal targeting strategies for animal oral vaccines - Meijun Yu; Yue Li; Zhaojun Wang; Ping Han; Yanping Jiang; Wen Cui; Yijing Li; Lijie Tang; Shuo Jia; Hongzhe Zhao; Yingying Ma; Jiaxuan Li; et al. (Veterinary Microbiology, 2026)

Component-specific microbial degradation and humification mechanisms of typical kitchen waste during winter hyperthermophilic composting in northeastern China - Youzhao Wang; Bingzhen Li; Jiacheng Li; Chaoyue Zhao; Xu Li; Yanping Zhang; Shujie Hou; Feng Ma; Ziwei Dai; Qiyu Gong; Xinchang Zhou; Fuxin Yang; et al. (Journal of Environmental Management, 2026)

Inhibition of potato common scab by Bacillus subtilis XT11 and its reshaping of the microbial community in potato geocaulosphere soil - Ning Liu; Minghao Lv; Yongdong Wang; Huimin Ma; Wei Fan; Junjie Ma; Jiguang Wang; Yanping Gao; Jinbiao Ma; Bo Zhou; Wenchong Shi; Zheng Gao (World Journal of Microbiology and Biotechnology, 2026)

Structural equation modeling revealed optimized ridge-furrow configuration integrated with straw-soil crust enhancing carbon sequestration and sainfoin yield in semiarid agroecosystems - Abdul Qadeer; Qi Wang; Rizwan Azim; Xiaole Zhao; Wen Ma; Ibrahim Awuku; Fujia Li; Qinglin Liu; Yanping Liu; Bing Liu; Xuchun Li; Muhammad Sanaullah; et al. (Computers and Electronics in Agriculture, 2026)

Divergent responses of maize and soybean to intercropping: Insights from arbuscular mycorrhizal fungi diversity, colonization, and related-genes expression - Shihui Yu; Xinru Liu; Ling Liu; Yanping Ma; Baohong Liu; Wuyan Xiang; Ying Zhang; Peiyong Liu; Chen Feng; Caixia Sun (Plant and Soil, 2026)

Bypassing Typhoons Cause Three-dimensional Dramatic Changes in Temperature and Ocean Heat Content of the Yellow Sea and Bohai Sea: A Case Study with Super Typhoon Maysak (2020) - Fangguo Zhai; Junyan Zhang; Yucheng Wang; Yujie Dong; Yanping Ma; Cong Liu; Zizhou Liu (Advances in Atmospheric Sciences, 2026)

Thermally driven polymer disentanglement: An overlooked Key pathway in PBAT-microplastic aging during composting - Yanping Zhang; Xu Li; Youzhao Wang; Fuxin Yang; Chaoyue Zhao; Shujie Hou; Bingzhen Li; Ziwei Dai; Yang Yun; Feng Ma; Liying Hao; Tong Zhu (Journal of Hazardous Materials, 2026)

Spatially stratified humification mechanisms in industrial-scale negative-pressure aerated thermophilic composting: Dominant pathways driven by temperature gradients and microbial succession - Shujie Hou; Youzhao Wang; Xu Li; Yanping Zhang; Xiaolong Gao; Jiedong Hao; Bingzhen Li; Ziwei Dai; Feng Ma; Fuxin Yang; Chaoyue Zhao; Tong Zhu (Journal of Environmental Chemical Engineering, 2026)

Long-distance lateral migration, accumulation and dissipation of natural gas in the northeastern Ordos Basin, China - Yang Qin; Chiyang Liu; Junfeng Zhao; Faqi He; Wei Zhang; Yanping Ma; Lihua Yang; Deyong Shao; Nan Du; Fuyu Chen (Gondwana Research, 2026)

Targeting Phospholipid Metabolism as an Effective Hearing Protection Strategy - Huanyu Mao; Wenli Ni; Lupeng Ma; Xiang Li; Yanping Zhang; Yuzheng Zhao; Wenyan Li; Huawei Li; Yan Chen (Neuroscience Bulletin, 2026)

The effect of CD40 agonist antibody therapy on the pancreatic cancer microenvironment - Yilan Ma; Jin Ding; Yanping Chen (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Chronological and geochemical constraints on the origin and timing of carbonate-cemented sandstones in the Middle Jurassic Zhiluo Formation, northeastern Ordos Basin, China - Yang Qin; Chiyang Liu; Junfeng Zhao; Yanping Ma; Lihua Yang; Nan Du (Marine and Petroleum Geology, 2025)

Stage-specific bacterial-fungal synergy in industrial-scale hyperthermophilic composting: Community assembly dynamics and modular networks drive humification - Chaoyue Zhao; Youzhao Wang; Feng Ma; Xu Li; Yanping Zhang; Shujie Hou; Bingzhen Li; Xiaodan Zhang; Fuxin Yang; Liying Hao; Tong Zhu (Journal of Environmental Management, 2025)

Multifunctional groups improved photoluminescence efficiency of hot exciton materials for blue OLEDs with a maximum external quantum efficiency exceeding 12 % - Xiaofen Zhuang; Yuwei Xu; Ruicheng Wang; Tingting Cao; Jinxiang Li; Zhiju Chen; Yueling Ma; Dehua Hu; Yaocheng Jin; Wen-cheng Chen; Xianwei Li; Shaomin Ji; et al. (Chemical Engineering Journal, 2025)

Selenium-Enriched Lactiplantibacillus plantarum ZZU 8–12 Regulates Intestinal Microbiota and Inhibits Acute Liver Injury - Yanping Wang; Hengyu Ma; Haolong Li; Yuhang Huang; Yupeng Tang; Xiaoxue Tang; Pintian Sun; Zhongfang Tan; Huili Pang; Fengyuan Yang (Probiotics and Antimicrobial Proteins, 2025)

Complete genome sequence and molecular characterization of a novel potyvirus (sweet potato virus H) infecting sweet potato - Wei Tang; Jukui Ma; Yanping Tian; Xiao Yin; Jingwei Chen; Dongjing Yang; Fangyuan Gao; Zhao Liang; Cong Tong; Chengling Zhang; Houjun Sun (Archives of Virology, 2025)

A potent and selective PROTAC degrader of CDK9 as effective inhibitor of HIV-1 RNA synthesis - Bo Yang; Ling Ma; Xiaotang Yang; Jiajia Wen; Weiyi Yin; Siqi Li; Yingjie Ji; Ying Wang; Shan Cen; Yanping Li (Molecular Diversity, 2025)

Naringenin attenuates Mandarin fish ranavirus (MRV)-induced hyperinflammation through the inhibition of MAPK and NF-κB signaling pathways - Ziye Zhang; Yanping Ma; Xinru Gao; Chaojiao Hu; Le Hao; Huijie Lu; Yugu Li; Zhenxing Liu (Fish & Shellfish Immunology, 2025)

Adapting to hypo-salinity: Molecular mechanisms in giant clams and symbionts with implications for coral reef resilience under climate change - Zhen Zhao; Xixi Duan; Tao Zhang; Siqi Bi; Zohaib Noor; Shuming Guo; Zonglu Wei; Yinjie Zhang; Yanping Qin; Haitao Ma; Ying Pan; Ziniu Yu; et al. (Environmental Research, 2025)

Suitable ridge width and straw length for alfalfa production under ridge-furrow rainwater harvesting compacted with chopped straw-soil crust in semiarid regions - Rizwan Azim; Qi Wang; Xuchun Li; Abdul Qadeer; Xiaole Zhao; Ibrahim Awuku; Wen Ma; Qinglin Liu; Yanping Liu; Bing Liu (Plant and Soil, 2025)

Insights into stress response pathways and potential triterpene accumulation mechanisms induced by friction damage in kiwifruit - Fan Yang; Yuchun Wang; Fangzhi Wu; Sike Wang; Yuduan Ding; Yue Chen; Qinggang Zhu; Yanping Ma (Postharvest Biology and Technology, 2025)

Genome-wide identification of ApeC domain-containing protein and revealing the function of ChACP-1.10 in oyster mucosal immunity - Tianxiang Lin; Lu Liu; Liang Zeng; Congxin Zhao; Shu Xiao; Haitao Ma; Jun Li; Fan Mao; Yanping Qin; Yuehuan Zhang; Yang Zhang; Zhiming Xiang; et al. (Fish & Shellfish Immunology, 2025)

Exploring the symbiotic resilience of boring giant clams and zooxanthellae during heatwave conditions: An investigation into strategic countermeasures - Zhen Zhao; Siqi Bi; Liqiang Zhao; Zohaib Noor; Shuming Guo; Zonglu Wei; Xixi Duan; Yanping Qin; Haitao Ma; Ying Pan; Ziniu Yu; Kotaro Shirai; et al. (Aquaculture, 2025)

Expert consensus on cryosurgery therapy of mucosal melanoma on head and neck - Yadong Wu; Guoxin Ren; Moyi Sun; Zhangui Tang; Longjiang Li; Jian Meng; Zhijun Sun; Shaoyan Liu; Yue He; Wei Shang; Bo Li; Jie Zhang; et al. (Cryobiology, 2025)

Stem nematode disease resistance-conferring gene identification in sweet potato using combined BSA-Seq and BSR-Seq analyses - Shouchen Qiao; Jingwei Chen; Yawei Li; Yannan Wang; Jukui Ma; Zhihe Kang; Qianqian Bian; Guozheng Cao; Guorui Zhao; Guohong Yang; Yanping Fan; Houjun Sun; et al. (Planta, 2025)

DNA damage repair (DDR) related prognostic risk model in multiple myeloma based on single-cell and bulk sequencing - Hongxiu Liu; Zhihua Li; Yihua Wang; Can Li; Kaiqing Yan; Yanping Ma (DNA Repair, 2025)

Apoptosis in spotted sea bass brain and astroglia-like cell line implies a possible pathogenesis of Lateolabrax maculatus iridovirus infection - Jingjing Xu; Yanping Ma; Le Hao; Zhenxing Liu (Fish Physiology and Biochemistry, 2025)

The poleward expansion of the Hadley Cell has weakened the winter circulation in a midlatitude semi-enclosed shelf sea over the past six decades - Fangguo Zhai; Hao Li; Yanping Ma; Yucheng Wang; Yujie Dong; Zizhou Liu; Yanzhen Gu; Peiliang Li (Climate Dynamics, 2025)

The independent and joint effects of meteorological factors on influenza: A nationwide time series study in China - Mengen Guo; Yunfei Zhang; Jianxiong Hu; Aga Zheng; Guanhao He; Xiaokun Yang; Hongting Zhao; Tao Liu; Fengrui Jing; Ziqiang Lin; Yanping Zhang; Maigen Zhou; et al. (Urban Climate, 2025)

Fabrication of biodegradable mulch film based on polylactic acid waste liquid - Dongfang Wang; Zerong Song; Xianghai Kong; Jie Wu; Jinjing Xu; Jinghong Ye; Yanping Zhu; Rongjun Zhang; Xiaoli Ma; Gang Li; Shifang Xu; Dongqing Cai (Chemical Engineering Journal, 2025)

Trait segregation and growth characteristics of the F2 generation hybrids between Crassostrea dianbaiensis and C. iredalei - Jiangwei Li; Ying Pan; Qinggan Xing; Jinhui Wu; Haitao Ma; Weitao Wan; Chao Yue; Zhongyu Wang; Jun Li; Ziniu Yu; Yanping Qin; Yuehuan Zhang (Aquaculture International, 2025)

Comparison of genetic diversity and population structure of Saccostrea mordax lineages A, B, and C across South China Sea and Celebes Sea - Yinjie Zhang; Haitao Ma; Chenghui Han; Zhen Zhao; Zonglu Wei; Xixi Duan; Jiangwei Li; Yanping Qin; Jun Li; Ziniu Yu; Ying Pan; Yuehuan Zhang (Frontiers in Marine Science, 2025)
Saccostrea mordax is an ecologically important bivalve species and a potential genetic resource for oyster breeding that inhabit in the Indo-Western Pacific region, characterized by three distinct lineages: A, B, and C. However, limited information is available about its genetic variation and genetic structure. The present study was conducted to study genetic diversity and population structure of S. mordax lineages A, B, and C based on mitochondrial COI gene data across the South China Sea and Celebes Sea. The UPGMA phylogenetic tree among populations, BI phylogenetic tree among individuals and median network revealed three main clusters, corresponding to S. mordax lineages A, B, and C. The results of K2P sequence divergence, pairwise Φ st, gene flow and AMOVA indicated clear genetic differences among the lineages, combined with sympatric in all 7 geographical populations, these suggests lineages A and B are transitional periods of new species formation. Moreover, different patterns of population subdivision were found within lineages A, B and C. In lineage A, significant genetic differentiation was only observed between YM (Celebes Sea) and other populations (South China Sea), with a significant correlation between geographical distance and genetic distance among populations. In lineages B and C, there was no genetic differentiation between YM (Celebes Sea) and other populations (South China Sea), and no significant correlation between genetic distance and geographical distance among populations. The population history analyses indicated that populations of lineage A have experienced a recent sudden expansion, while populations of lineages B and C were large stable. These findings are essential for the conservation, sustainable utilization, and ecological restoration of S. mordax .

Global prevalence of Porcine Astrovirus: A systematic review and meta-analysis - Xiaoyu Ge; Yize Li; Feipeng Zhao; Xin’ao Ma; Jiaxuan Li; Yanping Jiang; Wen Cui; Xiaona Wang; Lijie Tang (Preventive Veterinary Medicine, 2025)

Offspring performance of backcrossing between hybrid line of Crassostrea dianbaiensis ♀ × Crassostrea iredalei ♂ and their parental species - Jiangwei Li; Yanping Qin; Qinggan Xing; Jinhui Wu; Haitao Ma; Weitao Wan; Chao Yue; Zhongyu Wang; Jun Li; Ziniu Yu; Ying Pan; Yuehuan Zhang (Aquaculture, 2025)

Effects of simulated microgravity on dental pulp stem cell stemness - Huailong Hou; Zhengjun Qiu; Jingyi Che; Yanping Li; Jingxuan Sun; Weiwei Zhang; Jinjie Ma; Shuang Zhang; Mengdi Li; Yumei Niu; Lina He (Journal of Molecular Histology, 2025)

Growth performance of two brackish oysters (Crassostrea iredalei and Crassostrea dianbaiensis) and their hybrids in subtropical sea area - Jiangwei Li; Ying Pan; Jinhui Wu; Haitao Ma; Weitao Wan; Chao Yue; Shengyong Li; Zhongyu Wang; Jun Li; Ziniu Yu; Yanping Qin; Yuehuan Zhang (Aquaculture, 2025)

Lycorine provides antiviral activities against mandarin fish ranavirus via suppressing apoptosis and activating type I interferon pathway - Mengyan Jia; Yanping Ma; Le Hao; Ziqian Tao; Jingya Wang; Sentai Liao; Hui Guo; Zhenxing Liu (Aquaculture, 2025)

Automated calibration of Noah-MP land surface model for improved irrigation representation in the North China Plain - Danqiong Dai; Yanping Li; Liang Chen; Fei Chen; Zhenhua Li; Zhe Zhang; Prasanth Valayamkunnath; Li Xu; Cenlin He; Zhuguo Ma (Journal of Hydrology, 2025)

Enhancing humification in high-temperature composting: Insights from endogenous and exogenous heating strategies - Chaoyue Zhao; Feng Ma; Youzhao Wang; Xu Li; Yanping Zhang; Zhipeng Wang; Wei Xiong; Xiaolong Gao; Yongguang Ma; Fuxin Yang; Tong Zhu (Bioresource Technology, 2025)

Three-dimensional changes in temperature and circulation caused by northwestward-moving typhoons in a temperate semi-enclosed shelf sea in summer - Yanping Ma; Fangguo Zhai; Xingchuan Liu; Cong Liu; Zizhou Liu; Yanzhen Gu; Peiliang Li (Frontiers in Marine Science, 2025)
Due to the complex coastline and topography, changes of temperature and circulation in global shelf seas caused by typhoons have significantly region-specific three-dimensional structures. As one temperate semi-enclosed shelf sea, the Yellow Sea is highly susceptible to typhoons in summer. In August 2012 Typhoon Damrey moving northwestward over the Yellow Sea was observed to cause significant bottom temperature warming in the southern coastal waters of the Shandong Peninsula, but its impacts on the three-dimensional changes of temperature and circulation in the whole Yellow Sea and the underlying dynamics are still unclear. Using observations and high-resolution numerical simulations, we showed that during Damrey’s passage the South Yellow Sea exhibited spatially coherent surface cooling, particularly forming a distinct surface cooling band on the right side of the typhoon track. With the mixed layer deepening, the subsurface layer deepened and experienced temperature warming, especially on the right side of the typhoon track. The surface cooling and subsurface warming were primarily caused by strong wind-enhanced vertical mixing. In the deep layer, temperature exhibited pronounced warming in the southern coastal waters of the Shandong Peninsula but cooling in a southeast-northwest band along the bottom slope just off the Subei Shoal. Bottom temperature warming in the southern coastal waters of the Shandong Peninsula was caused by coastal downwelling resulting from upper layer coastward Ekman transport. Conversely, vertically consistent temperature cooling just off the Subei Shoal was caused by coastward and upward advection of cold water across the temperature fronts and thermocline due to surface layer Ekman divergence. The intensity and spatial distributions of temperature cooling just off the Subei Shoal were related to the distance between the typhoon track and Subei Shoal. Closer proximity of the typhoon track to the Subei Shoal would lead to more pronounced bottom cooling. This study enriches our understanding of three-dimensional hydrodynamic changes induced by typhoons with different tracks in the Yellow Sea.

Genetic diversity and genetic structure in successive mass selected generations of tetraploid Pacific oysters (Crassostrea gigas), diploid Portuguese oysters (C. angulata) and their allotriploid oysters - Haitao Ma; Yanping Qin; Yinjie Zhang; Weitao Wan; Jingyue Huang; Na Mi; Zhen Zhao; Zhongyu Wang; Jiangwei Li; Jun Li; Ziniu Yu; Yuehuan Zhang (Aquaculture, 2025)

Enhanced antioxidant potential of In vitro gastrointestinal digestion products derived from abalone myofibrillar protein-glucose conjugates based on structural changes - Gengxin Hao; Yanwen Ma; A.YiJiang Akemujiang; Yanping Bai; Peng Ye; Xujian Qiu; Shuting Lin (Food Bioscience, 2025)

Corrigendum to “Hybridization and growth characteristics of interspecific crosses between Crassostrea hongkongensis and Crassostrea iredalei” [Aquaculture, Volume 595, Part 2, 30 January 2025, 741656] - Jiangwei Li; Ying Pan; Qinggan Xing; Haitao Ma; Chao Yue; Weitao Wan; Jinhui Wu; Zhongyu Wang; Shengyong Li; Jun Li; Ziniu Yu; Yanping Qin; et al. (Aquaculture, 2025)

First successful inducing gynogenesis in Crassostrea angulata by inactivated tetraploid Crassostrea gigas sperm - Weitao Wan; Yanping Qin; Jinhui Wu; Haitao Ma; Chao Yue; Shengyong Li; Jiangwei Li; Zhongyu Wang; Jun Li; Anning Suo; Dewen Ding; Ziniu Yu; et al. (Aquaculture, 2025)

Hybridization and growth characteristics of interspecific crosses between Crassostrea hongkongensis and Crassostrea iredalei - Jiangwei Li; Ying Pan; Qinggan Xing; Haitao Ma; Chao Yue; Weitao Wan; Jinhui Wu; Zhongyu Wang; Shengyong Li; Jun Li; Ziniu Yu; Yanping Qin; et al. (Aquaculture, 2025)

Synthesis and Characterization of Efficient Adsorbents for Methylene Blue Based on Graphene Oxide/β-cyclodextrin Composites - Yanping Qu; Hongcui Li; Ibrahim Yakub; Wen He; Wenchan Dong; Mohamad Hardyman Barawi; Sirui Wang; Huimin Ma; Zhenpeng Zhu (Water, Air, & Soil Pollution, 2025)

Anti-inflammatory, anti-colitis, and antioxidant effects of columbianadin against DSS-induced ulcerative colitis in rats via alteration of HO-1/Nrf2 and TLR4-NF-κB signaling pathway - Yanping Zhang; Ping Cao; Dongyuan Qin; Ying Zhao; Xing Chen; Peng Ma (Inflammopharmacology, 2025)

Mandarin Fish Ranavirus ( MRV ) Infection Induced Inflammation and Histologic Lesions in the Gut of Mandarin Fish - Xinru Gao; Ziye Zhang; Yanping Ma; Le Hao; Wen Huang; Zhenxing Liu; Yugu Li (Journal of Fish Diseases, 2025)
Mandarin fish ranavirus (MRV) is widely spread in China and causes huge economic losses to the mandarin fish ( Siniperca chuatsi ) aquaculture. However, the pathogenesis of MRV is still unclear. In the present study, mandarin fish were artificially infected with MRV, and then different gut compartments from diseased fish were subjected to histologic analysis by H&E staining, quantification of proinflammatory genes and MRV copies by qPCR. MRV‐MCP protein expression was assessed using indirect fluorescence assay (IFA) and immunohistochemistry. Proliferation of IgM + B cells was evaluated by indirect fluorescence assay (IFA). Then, we found that MRV infection caused serious histologic lesions along with inflammatory cell infiltration, especially in the foregut. A significant accumulation of IgM + B cells was detected in the foregut (~6.5‐fold) and hindgut (~3.3‐fold), respectively. The expression of inflammation‐related genes such as IL‐1β, IL‐6, IL‐8, TNF‐α, CSF1r and NCF1 was significantly upregulated in the foregut, varying from ~2.8‐fold to ~11.9‐fold. In addition, MRV exhibited foregut tropism, according to the investigation of viral loads and MCP protein expression. Overall, our findings indicated that MRV‐induced hyperinflammation in the gut eventually led to enteritis. This study provided new insights into uncovering the pathogenesis of MRV infection.

Analysis of molecular identity and function of putative serotonin receptors in the Giant clam (Tridacna crocea) and the potential role of 5-HT1D-like receptor in reproduction - Xiaogang Yang; Zohaib Noor; Shuming Guo; Zhen Zhao; Borui Cai; Guozhao Huang; Haitao Ma; Yanping Qin; Ziniu Yu; Jun Li; Yuehuan Zhang (Aquaculture, 2024)

Assessing the feasibility of adjusting the dry matter content utilizing corn grits and cottonseed meal and inoculating with Lactiplantibacillus plantarum in the production of fermented feed from kitchen waste - Yupeng Tang; Fengyuan Yang; Huili Pang; Shanshan Zhao; Hengyu Ma; Haolong Li; Yuhang Huang; Pintian Sun; Xiaoxue Tang; Yanping Wang (Process Safety and Environmental Protection, 2024)

A study on the structure-functionality relationship of Solenaia oleivora protein under high-intensity ultrasonication processing - Wanwen Chen; Wu Jin; Xueyan Ma; Haibo Wen; Yanping Li; Gangchun Xu; Pao Xu; Hao Cheng (Food Chemistry, 2024)

Numerical simulation and deep-sea experiment validation for the cathodic protection design of aluminum alloy framework - Tigang Duan; Yu Zhang; Li Ma; Shaohua Xing; Yanping Liu; Wenshan Peng; Haibing Zhang; Jian Hou (Ocean Engineering, 2024)

Corrigendum to “Genetic improvement of aquaculture performance for tetraploid Pacific oysters, Crassostrea gigas: A case study of four consecutive generations of selective breeding” [Aquaculture 563 (2023) 738910] - Weitao Wan; Yanping Qin; Gongpengyang Shi; Shengyong Li; Qingliang Liao; Haitao Ma; Jun Li; Anning Suo; Dewen Ding; Ziniu Yu; Yuehuan Zhang (Aquaculture, 2024)

Successive selection responses of tetraploid Crassostrea angulata: Comparison of growth, survival, sex ratio and ploidy composition between selected and unselected groups - Yanping Qin; Weitao Wan; Jiangwei Li; Chao Yue; Zhongyu Wang; Qinggan Xing; Haitao Ma; Jun Li; Ziniu Yu; Yuehuan Zhang (Aquaculture, 2024)

ChCaspase-1 cleaves ChGasdermin-E, inducing pyroptosis, and participates in the bacterial defence of the oyster Crassostrea hongkongensis - Liang Zeng; Tianxiang Lin; Lu Liu; Congxin Zhao; Ruwen Yang; Shu Xiao; Fan Mao; Yanping Qin; Haitao Ma; Yuehuan Zhang; Yang Zhang; ZiniuYu; et al. (Aquaculture, 2024)

Two-stage hydrothermal liquefaction of Spirulina: Experimental observations, energy analysis and techno-economic assessment - Hongwei Pang; Yanping Feng; Xinru Ma; Qirong Yang; Zhaoying Li (Process Safety and Environmental Protection, 2024)

Upcycling of nutrients from kitchen waste: Integration of anaerobic digestion system and microbial protein production system - Qile Zhu; Kangjian Gao; Qi Sun; Chuan Ma; Yuxing Luo; Zijin Niu; Yanping Liu; Ziyi Yang (Journal of Environmental Management, 2024)

Adsorption mechanism and remediation of heavy metals from soil amended with hyperthermophilic composting products: Exploration of waste utilization - Feng Ma; Tong Zhu; Youzhao Wang; Shuichi Torii; Zhipeng Wang; Chaoyue Zhao; Xu Li; Yanping Zhang; Haoyu Quan; Chunli Yuan; Liying Hao (Bioresource Technology, 2024)

Cellular Senescence-Related Long Non-coding RNA Signatures Predict Prognosis in Juvenile Osteosarcoma - Peng Zhao; Junli Chang; YeKai Chen; Xingyuan Sun; Xiaoping Ma; Chujie Zhou; Lei Zhou; Yongjun Wang; Yanping Yang (Phenomics, 2024)
Osteosarcoma is the most common malignant bone tumor and is frequently diagnosed in juvenile. Cellular senescence is a fundamental hallmark of osteosarcoma and plays a vital role in the initiation and progression of aging and tumorigenesis. Long non-coding RNAs (lncRNAs) are implicated in tumorigenesis. In this study, six cellular senescence-related lncRNAs with independent prognostic significance in juvenile osteosarcoma patients were identified through univariate Cox regression analysis, least absolute shrinkage and selection operator (LASSO) regression analysis, and multivariate Cox regression analysis. Prognostic significance was further confirmed by Kaplan–Meier (KM) survival curves, co-expression interaction networks, and sankey diagrams. A prognostic model of cellular senescence-related genes in juvenile osteosarcoma patients was then constructed using multivariate Cox regression analysis based on these six genes. High- and low-risk groups were identified according to the median risk score calculated by the prognostic model. The favorable prognostic significance of this model was demonstrated through survival curves, receiver operating characteristic (ROC) curves, distribution scatter plots and lncRNA expression heatmaps. Furthermore, cellular senescence-related lncRNAs were validated by enrichment analysis, immunological correlation analysis, m 6 A correlation analysis, and drug sensitivity correlation analysis. These findings are important for improving the prognosis of juvenile osteosarcoma patients and understanding the mechanisms underlying cellular senescence in juvenile osteosarcoma development.

Targeting PI3K/Akt in Cerebral Ischemia Reperfusion Injury Alleviation: From Signaling Networks to Targeted Therapy - Ting Zheng; Taotao Jiang; Hongxiang Ma; Yanping Zhu; Manxia Wang (Molecular Neurobiology, 2024)

Evolutionary trajectory of TRPM2 channel activation by adenosine diphosphate ribose and calcium - Cheng Ma; Yanping Luo; Congyi Zhang; Cheng Cheng; Ning Hua; Xiaocao Liu; Jianan Wu; Luying Qin; Peilin Yu; Jianhong Luo; Fan Yang; Lin-Hua Jiang; et al. (Science Bulletin, 2024)

Feasibility exploration and comparative analysis of interspecific hybridization between Crassostrea hongkongensis and Crassostrea dianbaiensis - Jiangwei Li; Yanping Qin; Zhongli Peng; Weitao Wan; Chao Yue; Zhongyu Wang; Haitao Ma; Qinggan Xing; Jun Li; Ziniu Yu; Ying Pan; Yuehuan Zhang (Aquaculture, 2024)

Preparation of ternary composite film TiO2/Fe2O3/Ti3C2 for photoelectrocatalytic degradation of organic pollutants and bacterial inactivation in water - Yanping Ma; Jialin Gu; Xinshang Li; Wenquan Zhou; He Wang; Rui Zhang; Jiangang Jiang (Journal of Environmental Chemical Engineering, 2024)

ChRIPK1 caused necroptosis signaling pathway deficiency in Crassostrea hongkongensis - Yucheng Yang; Liang Zeng; Tianxiang Lin; Lu Liu; Congxin Zhao; Shu Xiao; Haitao Ma; Jun Li; Fan Mao; Yanping Qin; Yuehuan Zhang; Yang Zhang; et al. (Fish & Shellfish Immunology, 2024)

Response of water quality in major tributaries to the difference of multi-scale landscape indicators in Dongting Lake basin, China - Yang Bai; Zhifei Ma; Yanping Wu; Hailin You; Jinying Xu (Environmental Science and Pollution Research, 2024)

A strategy to assess the use-phase carbon footprint from energy losses in electric vehicle battery - Boran Yang; Chenran Du; Hang Zhang; Xiaoli Ma; Xueling Shen; Dong Wang; Zhanglong Yu; Qian Huang; Danni Gao; Yanping Yin; Yanyan Fang; Ran Xu (Journal of Cleaner Production, 2024)

Resistance of an intertidal oyster(Saccostrea mordax)to marine heatwaves and the implication for reef building - Shuming Guo; Jun Li; Xiaogang Yang; Yanping Qin; Yuexin Zhao; Jinkuan Wei; Haitao Ma; Ziniu Yu; Liqiang Zhao; Yuehuan Zhang (Science of The Total Environment, 2024)

Enhanced Sb(V) removal of sulfate-rich wastewater by anaerobic granular sludge assisted with Fe/C amendment - Qi Li; Yanping Zhu; Nan Jiang; Jun Li; Yanbiao Liu; Xiaoguang Chen; Xiaoyang Xu; Huangyingzi Wang; Yimeng Ma; Manhong Huang (Science of The Total Environment, 2024)

Phytoplankton community responses to the combined effects of internal waves and anticyclonic eddies shed from the Kuroshio intrusion - Yanping Zhong; Xiaolin Bai; Edward A. Laws; Wenfang Lu; Zhida Huang; Wupeng Xiao; Jixin Chen; Lingqi Ma; Xin Liu; Bangqin Huang (Ocean Dynamics, 2024)

Characterization of a membrane Fcγ receptor in largemouth bass (Micropterus saloumoides) and its response to bacterial challenge - Jingya Wang; Jing Wu; Yanping Ma; Le Hao; Wen Huang; Zhenxing Liu; Yugu Li (Fish Physiology and Biochemistry, 2024)

Unlocking the potential of biochar: an iron-phosphorus-based composite modified adsorbent for adsorption of Pb(II) and Cd(II) in aqueous environments and response surface optimization of adsorption conditions - Xu Li; Yuan Chi; Feng Ma; Xiaoxin Wang; Rui Du; Zhipeng Wang; Xiaoyan Dang; Chaoyue Zhao; Yanping Zhang; Shumin He; Youzhao Wang; Tong Zhu (Environmental Science and Pollution Research, 2024)

Growth, survival and reproductive traits of chemical induced and tetraploid-derived triploid Hong Kong oysters (Crassostrea hongkongensis) - Yanping Qin; Weitao Wan; Jiangwei Li; Zhongyu Wang; Haitao Ma; Jun Li; Ziniu Yu; Yuehuan Zhang (Aquaculture, 2024)

The feeding strategies of the antarctic lanternfish electrona antarctica (pisces: myctophidae) in the amundsen and cosmonaut seas (southern ocean), assessed with a classification tree analysis - Mi Duan; Chi Zhang; Yanping Luo; Libao Gao; Guankui Liu; Chunlin Liu; Yongming Sun; Jianchao Li; Shuyang Ma; Wenchao Zhang; Yongjun Tian (Polar Biology, 2024)

Changes of MRGs and ARGs in Acinetobacter sp. SL-1 used for treatment of Cr(VI)-contaminated wastewater with waste molasses as carbon source - Hui Wu; Rongxiao Wang; Yanping Ma; Tian C. Zhang; Yexing Yu; Jirong Lan; Yaguang Du (Science of The Total Environment, 2024)

Controlled atmosphere storage alleviates the browning of walnut (Juglans regia L.) fruit through enhancing GABA-mediated energy metabolism - Niu Ye; Dongli Zhang; Shan Liu; Yongqi Zhang; Yifan Wang; Yan Tang; Xiangna Yang; Jiahao Chai; Yanping Ma; Huiling Ma (Postharvest Biology and Technology, 2024)

Phenotypic traits of reciprocal tetraploid hybrids derived from tetraploid Crassostrea gigas and tetraploid Crassostrea angulata - Chao Yue; Yanping Qin; Weitao Wan; Gongpengyang Shi; Shengyong Li; Jiangwei Li; Zhongyu Wang; Haitao Ma; Jun Li; Ziniu Yu; Yuehuan Zhang (Aquaculture, 2024)

Modified nano zero-valent iron coupling microorganisms to degrade BDE-209: Degradation pathways and microbial responses - Jing Ma; Yingping Li; Xing Zhang; Jingjing Li; Qingqi Lin; Yanping Zhu; Zhepu Ruan; Zhuobiao Ni; Rongliang Qiu (Journal of Hazardous Materials, 2024)

Effects of wastewater treatment plant effluent on microbial risks of pathogens and their antibiotic resistance in the receiving river - Zijian Xiao; Yuanyuan Qin; Li Han; Yifan Liu; Ziyi Wang; Yanping Huang; Yujing Ma; Yina Zou (Environmental Pollution, 2024)

Characterization of the Ovarian Development and Associated Factors during the Breeding Migration of Coilia nasus in the Yangtze River - Shuwei Wei; Zhong Hua; Yanping Yang; Fengjiao Ma; Wei Han; Wei Zhang; Congping Ying; Yanmin Deng; Kai Liu (Fishes, 2024)
Coilia nasus is a typical anadromous migratory fish found in the lower reaches of the Yangtze River. Every year, C. nasus clusters offshore and swims upstream along the Yangtze River into the tributaries and lakes in the middle and lower reaches of the Yangtze River to breed. In this study, female C. nasus were collected as study subjects from the Chongming section of Shanghai, the Taizhou section of Jiangsu, and the Anqing section of Anhui. Their ovaries were used to examine tissue sections and investigate gene expression, including the follicle-stimulating hormone receptor (fshr), the luteinizing hormone receptor (lhr), kisspeptin-1 (kiss1), and forkhead box l2 (foxl2), which are related to reproductive development, while the serum levels of estrogen (including estradiol, E2) and progestins (including 17α,20β-dihydroxy-4-pregenen-3-one, 17α,20β-DHP) were also analyzed. Our results showed that, first, the growth period of the oocytes was small in stage II of ovarian development, in which both E2 and 17α,20β-DHP levels and gene expression were low. Then, in stage III, the growth period of the oocytes became large, and the yolk granules and oil droplets began to appear. Simultaneously, E2 and the expression of kiss1 and foxl2 were significantly elevated. Finally, stage IV was the period of a large amount of accumulation of nutrients in the oocytes, and 17α,20β-DHP levels and the expression of fshr and lhr were significantly elevated. These results enrich the theoretical study of ovarian development in the natural population of C. nasus, supplementing the biological basis of C. nasus reproduction and scientifically supporting the study of C. nasus population ecology and resource conservation.

Equal importance of humic acids and nitrate in driving anaerobic oxidation of methane in paddy soils - Yanan Bai; Yanping Wang; Lidong Shen; Bo Shang; Yang Ji; Bingjie Ren; Wangting Yang; Yuling Yang; Zhiguo Ma; Zhaozhong Feng (Science of The Total Environment, 2024)

Two-stage method recovery of metals from copper slag: Realize the resource utilization of all components - Lanbin Wang; Yangming Xu; Liang Tian; Yu Chen; Anju Yang; Guixiang Gan; Yanping Ma; Yaguang Du (Minerals Engineering, 2024)

Impact of cobalt recycling on China's electrification process: Assessing the potential reduction in cobalt demand from battery recycling - Lilong Chen; Xin Li; Yanping Luo; Wenli Tan; Qiaoying Ma; Minxi Wang; Jianbo Yang (Journal of Cleaner Production, 2024)

Understanding quality differences between kiwifruit varieties during softening - Fan Yang; Renkai Zhao; Jiangtao Suo; Yuduan Ding; Jiawei Tan; Qinggang Zhu; Yanping Ma (Food Chemistry, 2024)

A multifunctional emitter with synergistical adjustment of rigidity and flexibility for high-performance data-recording and organic light-emitting devices with “hot exciton” channel - Guowei Chen; Wen-Cheng Chen; Yaozu Su; Ruicheng Wang; Jia-Ming Jin; Hui Liang; Bingxue Tan; Dehua Hu; Shaomin Ji; Hao-Li Zhang; Yanping Huo; Yuguang Ma (Chemical Engineering Journal, 2024)

Impact of facemask debris on marine diatoms: Physiology, surface properties, sinking rate, and copepod ingestion - Fengyuan Chen; Zhen Zhang; Yanping Li; Hao Jiang; Yanfei Zhou; Hongbin Liu; Ke Pan; Jie Ma (Science of The Total Environment, 2023)

A novel antibacterial mechanism of atmospheric cold plasma against Staphylococcus aureus through degradation of cellular staphyloxanthin - Yupan Zhu; Hangbo Xu; Dongjie Cui; Renwu Zhou; Yanping Wang; Aswathi Soni; Gale Brightwell; Jie Zhuang; Ruonan Ma; Zhen Jiao (Innovative Food Science & Emerging Technologies, 2023)

Walnut green husk extract enhances the effect of chlorine dioxide on kernel quality and antioxidant properties of fresh-eating walnuts during their shelf life - Dongli Zhang; Niu Ye; Mingrui Li; Guoli Dai; Yanping Ma; Yifan Wang; Chaobin Liu; Huiling Ma (Food Chemistry, 2023)

RNA interference of NADPH-cytochrome P450 reductase increases the susceptibility of Aphis gossypii Glover to sulfoxaflor - Qiuling Tang; Xuchao Li; Yanping He; Kangsheng Ma (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Precise diagnosis of breast phyllodes tumors using Raman spectroscopy: Biochemical fingerprint, tumor metabolism and possible mechanism - Yifan Wu; Yaohui Wang; Chang He; Yan Wang; Jiayi Ma; Yanping Lin; Liheng Zhou; Shuguang Xu; Yumei Ye; Wenjin Yin; Jian Ye; Jingsong Lu (Analytica Chimica Acta, 2023)

Co-recovery of Mn and Fe from pyrolusite and copper slag with hydrometallurgy process: Kinetics and leaching mechanisms - Lanbin Wang; Yu Chen; Yangming Xu; Yanping Ma; Yaguang Du (Environmental Science and Pollution Research, 2023)

Controlled synthesis of CuS with different morphology and pollution control of Hg0 in non-ferrous smelting flue gas - Jin Zhao; Xueqian Wu; Yanping Ma; Wei Liu; Zhen Li; Songjian Zhao (Fuel, 2023)

Nanopore Structure and Multifractal Characteristics of Continental Shale Oil Reservoir: A Case Study from Ziliujing Shales in the Sichuan Basin - Youzhi Wang; Wei Li; Xiandong Wang; Zhiguo Wang; Weiqi Ma; Yanping Zhu; Mengdi Sun; Bo Liu; Lijuan Cheng; Xiaofei Fu (Journal of Marine Science and Engineering, 2023)
Thermal maturity of the shales from the Ziliujing Formation of the Jurassic age in the Sichuan Basin is in the hydrocarbon generation window, which makes it a candidate for shale oil and gas development. The meso- and macropore characteristics and heterogeneity of shales are important factors affecting the occurrence and development of oil and gas. However, the meso- and macropores of the Ziliujing shales have not been systematically studied. Thus, the mineral compositions and total organic carbon (TOC) of samples from this formation, as well as its pore structure, are analyzed by low-temperature N2 adsorption technique. Moreover, the heterogeneity of the pores was determined by multifractal analysis. The results show that the Ziliujing shales can be classified into three types according to the distributions of mineral compositions of carbonate and mixed and argillaceous shales. Results revealed that the smallest meso- and macropore volume (PV), the smallest specific surface area (SSA), and the largest average pore diameter (APD) occur in the carbonate shales. However, the largest PV and SSA and the smallest APD are observed in the argillaceous shales. The porosity of carbonate shales is mainly concentrated between 5 nm and 30 nm. Compared with carbonate shales, the porosity with pore sizes less than 30 nm of mixed and argillaceous shales shows a rapid increase. Furthermore, inorganic minerals are the main factors affecting the pore distributions, while TOC shows a weak effect. Herein, clay minerals significantly increase the mesopore volume and the pore number with a size of less than 30 nm. The Dq-q curves reveal that the meso- and macropore distributions of Ziliujing shales show multifractal behavior, but the multifractal characteristics of pores of various shales are distinctly different. The information dimension D1, the Hurst exponent H, and the width of the right side D0–D10 are key indicators to distinguish the local variations within the pore structure of different types of shales. The carbonate shales have the largest multifractal spectra width and the smallest D1 and H, while the opposite trend is found for the argillaceous shales. Clay minerals reduce the heterogeneity of the meso- and macropore distributions and increase the pore connectivity. Nevertheless, the carbonate minerals exhibit a reverse trend. Finally, it was found that TOC does not impact pore complexity as much. Collectively, this study supports our understanding of the occurrence of shale oil within various reservoir facies, thereby providing a guideline for future explorations in the Ziliujing Formation of the Jurassic age in the Sichuan Basin.

Extraction of rubidium and cesium from oilfield brine by the two-step adsorption–flotation method - Dezhen Fang; Miao Lu; Yanping Wang; Liang Ma; Kexin Li; Haining Liu; Huifang Zhang; Guosheng Shi; Zhijian Wu; Xiushen Ye (Minerals Engineering, 2023)

The reverse flow among parallel U-tubes in steam generator under natural circulation condition: A review - Hao Jianli; Ma Junjie; Huang Yanping; Chen Wenzhen; Yu Lei (Annals of Nuclear Energy, 2023)

The rhizosphere soil properties and bacteria community of poplar are affected by magnetic field under salt condition - Han Wenhao; Wang Nianzhao; Hu Jihuai; Yan Kun; Ma Fengyun; Tian Huimei; Wang Yanping (Rhizosphere, 2023)

Detoxification and resource utilization of soda ash chromite ore processing residue by copper slag - Lanbin Wang; Yangming Xu; Yanping Ma; Yu Chen; Anju Yang; Guixiang Gan; Yaguang Du; Yan Sun (Process Safety and Environmental Protection, 2023)

Fractionations of heavy metals and their correlations with magnetic susceptibility in soil from a typical alluvial island in the lower yangtze river, China - Cheng Wang; Rong Ma; Jianhua Wang; Cong Zhong; Yanping Zhao; Patrick Browne (Journal of Cleaner Production, 2023)

Climatological features of future MCSs over the Canadian Prairies using convection-permitting climate models - Yunsung Hwang; Xiao Ma; Richard Y.K. Agyeman; Yanping Li (Atmospheric Research, 2023)

Nitrogen addition regulates the growth of Pinus tabuliformis by changing distribution patterns of endogenous hormones in different organs - Yuhang Peng; Keli Chen; Guoliang Wang; Jiawei Tan; Furong Wei; Yanping Ma (New Forests, 2023)

Detection of depression marker ASS1 in urine by gold nanoparticles based dual epitope-peptides imprinted sensor - Hong Wei; Zixia Wang; Yanping Wang; Jing Ma; Yan Chen; Min Guo; Yuanyuan Li; Yongling Du; Fangdi Hu (Analytica Chimica Acta, 2023)

Comprehensive analysis of lncRNA-mRNA regulatory network in Populus associated with xylem development - Na Sun; Yufen Bu; Xinyuan Wu; Xiaocen Ma; Haobo Yang; Liang Du; Xiaojuan Li; Jianwei Xiao; Jinxing Lin; Yanping Jing (Journal of Plant Physiology, 2023)

Comparison between discarded facemask and common plastic waste on microbial colonization and physiochemical properties during aging in seawater - Jie Ma; Fengyuan Chen; Ciara Chun Chen; Zhen Zhang; Zihan Zhong; Hao Jiang; Junbao Pu; Yanping Li; Ke Pan (Journal of Hazardous Materials, 2023)

Associations between residential greenness and asthma and allergic rhinitis in children: A systematic review and meta-analysis - Wei Liu; Kailun Liu; Jiao Cai; Shuang Ma; Minghan Yang; Quan Yang; Yanping Yuan (Sustainable Cities and Society, 2023)

Effect of dietary Agriophyllum squarrosum on average daily gain, meat quality and muscle fatty acids in growing Tan lambs - Yanping Liang; Dan Jiao; Xia Du; Jianwei Zhou; Abraham Allan Degen; Fu Ran; Guancong Sun; Kaixi Ji; Xiukun Wu; Xindong Cheng; Xiaofei Ma; Chaoju Qian; et al. (Meat Science, 2023)

High expression of HOXC6 predicts a poor prognosis and induces proliferation and inflammation in multiple myeloma cells - Zhihua Li; Yaru Wang; Xiaoxu Hou; Luyao Guo; Yanling Li; Yanping Ma; Yanping Ma (Genes & Genomics, 2023)

Machine learning algorithm inversion experiment and pollution analysis of water quality parameters in urban small and medium-sized rivers based on UAV multispectral data - Yikai Hou; Anbing Zhang; Rulan Lv; Yanping Zhang; Jie Ma; Ting Li (Environmental Science and Pollution Research, 2023)

Enhanced trichloroethylene biodegradation: The mechanism and influencing factors of combining microorganism and carbon‑iron materials - Jing Ma; Manxi Xie; Nan Zhao; Yue Wang; Qingqi Lin; Yanping Zhu; Yuanqing Chao; Zhuobiao Ni; Rongliang Qiu (Science of The Total Environment, 2023)

Microscopic Analysis of Natural Fracture Properties in Organic-Rich Continental Shale Oil Reservoirs: A Case Study from the Lower Jurassic in the Sichuan Basin, China - Xuefeng Bai; Saipeng Huang; Xiandong Wang; Zhiguo Wang; Youzhi Wang; Weiqi Ma; Yanping Zhu; Mengdi Sun; Bo Liu; Xiaofei Fu; Lijuan Cheng; Likai Cui; et al. (Journal of Marine Science and Engineering, 2023)
Natural fractures are of paramount importance in storing carbon in shale oil reservoirs, where ultra-low porosity and permeability necessitate their essentiality for enhanced oil recovery. Therefore, comprehensively clarifying the characteristics of natural fractures in shale oil reservoirs is imperative. This paper focuses on investigating the microscopic features of natural fractures in organic-rich continental shale oil reservoirs that are commonly found in the Lower Jurassic strata of the Sichuan Basin, employing them as a representative example. Multiple methods were utilized, including mechanical testing, Kaiser testing, multi-scale CT scanning (at 2 mm, 25 mm, and 100 mm scales), and a numerical simulation of fluid seepage in fracture models. The results revealed that the in situ stress of the target seam displays the characteristic of σH > σv > σh, with σv and σh being particularly similar. The relatively high lateral stress coefficient (ranging from 1.020 to 1.037) indicates that the horizontal stresses are higher than the average level. Although the 2 mm CT scan provides a more detailed view of fractures and connected pores, it primarily exhibited more pore information due to the high resolution, which may not fully unveil additional information about the fractures. Thus, the 25 mm shale core is a better option for studying natural fractures. The tortuosity of the different fractures indicated that the morphology of larger fractures is more likely to remain stable, while small-scale fractures tend to exhibit diverse shapes. The simulations demonstrated that the stress sensitivity of fracture permeability is approximately comparable across different fracture scales. Therefore, our research can enhance the understanding of the properties of natural fractures, facilitate predicting favorable areas for shale oil exploration, and aid in evaluating the carbon storage potential of shale oil reservoirs.

The effect of in vitro digestion on the chemical and antioxidant properties of Lycium barbarum polysaccharides - Wenjun Zeng; Lulu Chen; Yanping Li; Jianlong Ma; Rui Yang; Jianbao Ding; Jin Yang (Food Hydrocolloids, 2023)

Fumigant toxicity and behavioral alterations of six plant essential oils against the red fire ant (Solenopsis invicta Buren) - Jiantao Fu; Zewen Ma; Lanying Wang; Yunfei Zhang; Yanping Luo (Environmental Science and Pollution Research, 2023)

Effects of grazing exclusion on vegetation community characteristics over 22 years in the Zoige alpine meadows from China - Xue Jiang; Li He; Yanping Qu; Banghong Jian; Dongzhou Deng; Mei Liu; Jingtian Yang; Yunlong Ma; Dechao Chen; Yi Huang (Acta Oecologica, 2023)

Studies of interspecific backcross between hybrids of (Crassostrea angulata ♀ × C. gigas ♂) and their two parental species - Gongpengyang Shi; Yanping Qin; Weitao Wan; Shengyong Li; Qingliang Liao; Haitao Ma; Jun Li; Yunqing Li; Yinyin Zhou; Yuehuan Zhang; Ziniu Yu (Aquaculture, 2023)

A magnetic adsorbent with metal-organic framework based on ammonium phosphomolybdenum heteropoly tungstate (AWP): Selective adsorption of Rb+ and Cs+ from aqueous resources and stripping with ammonium salts - Yanping Wang; Kexin Li; Liang Ma; Dezhen Fang; Miao Lu; Xiushen Ye; Haining Liu; Huifang Zhang; Xiaoli Tan; Zhijian Wu (Hydrometallurgy, 2023)

Genetic characteristics and growth patterns of the hybrid grouper derived from the hybridization of Epinephelus fuscoguttatus (female) × Epinephelus polyphekadion (male) - Liu Cao; Pan Chen; Xingrong Hou; Jun Ma; Ning Yang; Yanping Xu; Yanjin Zhang; Anqi Zhao; Jiyuan Zhang; Xinyu Li; Hai Huang (Journal of Fish Biology, 2023)
Hybridization is one of the primary methods used to cultivate farmed grouper species. The hybrid grouper derived from crossing Epinephelus fuscoguttatus (♀) and E. polyphekadion (♂) exhibits growth superiority over its parents. The genetic characteristics and growth patterns of the hybrid grouper have not yet been defined. This study confirms the ploidy level of the hybrid grouper (2 n = 48) using chromosome count analysis and flow cytometry. The 5S rDNA family was used to evaluate genetic diversity. Only one 5S class (~400 bp) was detected in the hybrid grouper, which could be used to distinguish between two different types based on nucleotide sequences, likely representing homologous unit classes from the female and male parental species. Growth patterns of 5–8‐month‐old hybrid groupers were also monitored. In this phase, a positive allometric growth pattern in body mass with total length was found. Body height and body mass were significantly correlated based on correlation and path coefficient, suggesting that body height could serve as an excellent index to increase body mass. These results aid our understanding of the genetic evolution of the hybrid grouper and inform the development of improved rearing techniques.

Comparative analysis of growth, survival and sex proportion among tetraploid-based autotriploid (Crassostrea gigas and C. angulata) and their allotriploid oysters - Yanping Qin; Gongpengyang Shi; Weitao Wan; Shengyong Li; Yunqing Li; Jun Li; Haitao Ma; Yuehuan Zhang; Ziniu Yu (Aquaculture, 2023)

Feasibility of interspecific hybridization between Iwagaki oyster, Crassostrea nippona and Portuguese oyster, Crassostrea angulata - Shengyong Li; Yanping Qin; Gongpengyang Shi; Weitao Wan; Qingliang Liao; Haitao Ma; Jun Li; Ziniu Yu; Ying Pan; Yuehuan Zhang (Aquaculture, 2023)

Genetic improvement of aquaculture performance for tetraploid Pacific oysters, Crassostrea gigas: A case study of four consecutive generations of selective breeding - Weitao Wan; Yanping Qin; Gongpengyang Shi; Shengyong Li; Qingliang Liao; Haitao Ma; Jun Li; Anning Suo; Dewen Ding; Ziniu Yu; Yuehuan Zhang (Aquaculture, 2023)

Eukaryotic community succession on discarded face masks in the marine environment - Jie Ma; Fengyuan Chen; Zhen Zhang; Yanping Li; Jingli Liu; Ciara Chun Chen; Ke Pan (Science of The Total Environment, 2023)

Comparison of biochemical composition, nutritional quality, and metals concentrations between males and females of three different Crassostrea sp. - Yanping Qin; Ru Li; Qingliang Liao; Gongpengyang Shi; Yinyin Zhou; Weitao Wan; Jun Li; Haitao Ma; Yuehuan Zhang; Ziniu Yu (Food Chemistry, 2023)

Fcγ receptor‐mediated phagocytosis pathway was involved in phagocytosis of mIgM + B lymphocytes from largemouth bass ( Micropterus salmoides ) - Jing Wu; Yifan Nie; Jingya Wang; Guoqing Feng; Le Hao; Yanping Ma; Yugu Li; Zhenxing Liu (Journal of Fish Biology, 2023)
The potential for phagocytosis has been proven in teleost B cells, but the research on the regulatory mechanism of phagocytosis remains lacking. In this study, three largemouth bass ( Micropterus salmoides ) (15 ± 5 g) were injected intraperitoneally with Nocardia seriolae (10 5 CFU/100 μl/fish) in vivo , and their spleen was collected at 72 h post‐infection for mRNA‐seq. After the de novo assembly of the paired‐end reads, 73,622 unigenes were obtained. Gene expression profiling revealed that 2043 unigenes were differentially expressed after N. seriolae infection, comprising 1285 upregulated and 758 downregulated unigenes ( q ‐value 0.05, log2FC > |2|) of which 181 genes were involved in phagocytosis. The Kyoto Encyclopaedia of Genes and Genomes (KEGG) analysis demonstrated that 12 differentially expressed genes (DEG) associated with phagocytosis were enriched in the Fcγ receptor‐mediated phagocytosis signalling pathway. In vitro , the phagocytic ability of mIgM + B lymphocytes was validated using indirect immunofluorescence assay (IIFA) and fluorescence activating cell sorter (FACS), and the phagocytosis rates of the mIgM + B lymphocytes incubated with a Lyn inhibitor had decreased from 18.533 ± 6.00% to 11.610 ± 4.236% compared with the unblocked group. These results suggested that the Fcγ receptor‐mediated phagocytosis signalling pathway had participated in the phagocytosis of B cells and provide further insight into the role of B cells in innate immunology.

Ectopic expression of NAC transcription factor HaNAC3 from Haloxylon ammodendron increased abiotic stress resistance in tobacco - Xiashun Liu; Xingfeng Zong; Xia Wu; Hao Liu; Jvdong Han; Zhengpei Yao; Yanping Ren; Li Ma; Bo Wang; Hua Zhang (Planta, 2022)

Adsorption of di (2-ethylhexyl) phthalate (DEHP) to microplastics in seawater: a comparison between pristine and aged particles - Ke Pan; Ciara Chun Chen; Lin Lin; Huo Xu; Fengyuan Chen; Yanping Li; Xiaoshan Zhu; Jie Ma; Wenlu Lan (Bulletin of Environmental Contamination and Toxicology, 2022)

Molecular phylogeny and divergence time estimates for native giant clams (Cardiidae: Tridacninae) in the Asia-Pacific: Evidence from mitochondrial genomes and nuclear 18S rRNA genes - Haitao Ma; Dongmei Yu; Jun Li; Yanping Qin; Yang Zhang; Zhiming Xiang; Yuehuan Zhang; Ziniu Yu (Frontiers in Marine Science, 2022)
Giant clams are conspicuous bivalves that inhabit in coral reefs. Among the giant clams, eight species of subfamily Tridacninae are the most common in the Asia-Pacific. However, very little is known about their evolutionary history. Here, we determined the complete mitochondria genome of Hippopus porcellanus , which was 29,434 bp in size and contained 13 protein-coding genes, 2 rRNAs and 23 tRNAs. The A+T composition of protein-coding regions was 57.99%, and the AT composition of the 3 rd codon position was 59.33%, of which in agreement with the invertebrate bias favoring codons ending in A or T. Analysis of phylogenetic relationships according to the concatenated nucleotide data set containing 18S rRNA gene and 13 protein-coding genes, the phylogenetic relationship was analyzed by Maximum likelihood and Bayesian inference methods. The results showed that T. maxima was placed with the clade comprising T. noae , T. squamosa , and T. crocea , in which T. squamosa was highly similar to T. crocea and is consistent with the results of the previous studies using15 mitochondrial markers and nuclear 18S rRNA. Moreover, the inferred divergence time of Tridacnidae species is generally consistent with the fossil record of Tridacnidae. The divergence time of H. porcellanus and H. hippopus was about 10.64 Mya, this result is in agreement with the speculation that H. porcellanus also originated in Miocene. The availability of molecular phylogeny and divergence time estimation provides information genetic relationship of Tridacninae, which could be helpful to the ecological research and conservation of giant clams.

Fungal dynamic changes in naturally fermented ‘Kyoho’ grape juice - Wenjuan Zhao; Zhiming Zhang; Yuhong Gao; Xiaozhen Liu; Chaojin Du; Fuxian Ma; Sujie Wang; Wanyuan Shi; Yanping Yang; Ruyou Deng; Hanyao Zhang (Archives of Microbiology, 2022)

Toxicity and Bioaccumulation of Copper in Phaeodactylum tricornutum Under Different Macronutrient Conditions - Beibei Zhou; Yue Zou; Jie Ma; Yanping Li; Ke Pan (Frontiers in Marine Science, 2022)
In this study, we investigated cell physiological and biochemical responses to copper (Cu) accumulation in the marine diatom Phaeodactylum tricornutum under different nitrogen (N) and phosphorus (P) conditions. Cells with sufficient N and P (+N+P) showed the highest total Cu concentrations and displayed a higher metal-tolerance ability. In the +N+P treatments, 36.5% of dissolved Cu was adsorbed on the frustules (cell walls), 54.9% was occluded in organelles, and 8.6% was in the soluble fraction. In comparison, cells with N and/or P shortages (+N−P, −N+P, and −N−P) adsorbed 10.8–13.1% of the total Cu onto their cell walls, 74.5–80% was occluded in organelles, and 9.2–12.4% was in the soluble fraction. The Cu 2+ influx on the +N+P cell wall was faster due to sufficient metal ligands on the cell walls and up-regulated metal-related transporters. A significant increase in protein content occurred under N and/or P shortages, which was accompanied by the inhibition of the antioxidative enzymatic system and cell membrane damage. Our findings indicate that N and P play an important role in both Cu adsorption (cell surface) and uptake (intracellular), and they provide multifaceted evidence of the Cu acquisition mechanism in P. tricornutum under different macronutrient conditions.

Study on the Individual Coloring Mechanism of Iridescent Cells in the Mantle of the Boring Giant Clam, Tridacna crocea - Yunqing Li; Yinyin Zhou; Jinkuan Wei; Gongpengyang Shi; Qingliang Liao; Shuming Guo; Zihua Zhou; Jun Li; Yanping Qin; Haitao Ma; Ziniu Yu; Yuehuan Zhang (Frontiers in Marine Science, 2022)
Giant clams are marine bivalves that inhabit Indo-Pacific coral reefs. The boring giant clam, Tridacna crocea , exhibits bright and conspicuous mantle coloration based on the specialized cells (iridocytes) that generate structural colors. In order to illustrate the coloring mechanism of individual iridocytes, the reflection spectra curve of iridocytes was obtained by a micro-hyperspectral imager. TEM images were obtained to show the inner nanostructures of iridocytes. FDTD simulation was conducted to analyze the relationship between the color of iridocytes and the unique lamellar structure. We found that the laminae in the regular arrangement within cells govern the coloration of individual iridocytes. With the gradual increase of lamellar thickness and spacing, the color of the structure varies from bright violet to orange-red, forming a full visible spectrum. This study provides a new understanding of the various colors produced by individual iridocytes.

Correction to: Spindle‑related brain activation in patients with insomnia disorder: An EEG‑fMRI study - Yan Shao; Guangyuan Zou; Serik Tabarak; Jie Chen; Xuejiao Gao; Ping Yao; Jiayi Liu; Yuezhen Li; Nana Xiong; Wen Pan; Mengying Ma; Shuqin Zhou; et al. (Brain Imaging and Behavior, 2022)

Spindle-related brain activation in patients with insomnia disorder: An EEG-fMRI study - Yan Shao; Guangyuan Zou; Serik Tabarak; Jie Chen; Xuejiao Gao; Ping Yao; Jiayi Liu; Yuezhen Li; Nana Xiong; Wen Pan; Mengying Ma; Shuqin Zhou; et al. (Brain Imaging and Behavior, 2022)

Microplastic Contamination on the Beaches of South China - Bingwen Chai; Yanping Li; Li Wang; Xiao-Tan Zhang; Yi-Ping Wan; Fengyuan Chen; Jie Ma; Wenlu Lan; Ke Pan (Frontiers in Marine Science, 2022)
Microplastics (MPs) have emerged as a pollutant of significant global concern. The sandy beach is a fragile environment that deserves our special attention with regard to MP contamination, as this area is a hotspot that accumulates large quantities of plastic waste. Notably, our current understanding of the MP distribution on beaches and the scale of contamination is far from sufficient. Hence, this study investigated the occurrence and characteristics of MPs on 14 beaches along the coast of South China. The MPs were ubiquitously distributed in the sand, most were small, less than 1 mm. A total of 18 types of polymers were identified in the sand, suggesting that diverse types of MPs are present on the beaches. Polyethylene, polypropylene, and polystyrene were the dominant types of MPs in most of our sampling sites. The MP abundance was higher in the upper layers (0–20 cm) of the beach than in the deeper layers (20–40 cm) of the sampling site when characterized by depth (Yangjiang beach). Our study demonstrates the extent and severity of MP pollution on the beaches of South China and provides implications for future remediation measures. More effort is needed to clarify the vertical distribution of MPs on beaches, especially for those MPs less than 1 μm.

The Innate Immune Response to Infection by Polyascus gregaria in the Male Chinese Mitten Crab (Eriocheir sinensis), Revealed by Proteomic Analysis - Yanping Yang; Fengjiao Ma; Juanjuan Dong; Lianxing Li; Ping Ren; Yuning Zhang; Yatao Wu; Yinping Wang; Kai Liu; Fang Zhang (Fishes, 2021)
The Chinese mitten crab (Eriocheir sinensis) is a representative catadromous invertebrate of the Yangtze River and a commercial species widely cultivated in China. Both cultivated and wild crabs suffer from a variety of parasites and pathogens, which can result in catastrophic economic losses in aquaculture revenue. Polyascus gregaria, a parasitic barnacle with a highly derived morphology, is specialized in invading these crabs. This study examines the immunological mechanism in E. sinensis infected with P. gregaria. Tandem mass tags (TMT), a specialized method of mass-spectrometry, was used to analyze the infection by P. gregaria resistance at the protein level. In the hepatopancreas of infected crabs, 598 proteins differentially expressed relating to physiological change, of which, 352 were upregulated and 246 were downregulated. Based on this differential protein expression, 104 GO terms and 13 KEGG pathways were significantly enriched. Differentially expressed proteins, such as ATG, cathepsin, serpin, iron-related protein, Rab family, integrin, and lectin, are associated with the lysosome GO term and the autophagy-animal KEGG pathways, both of which likely relate to the immune response to the parasitic P. gregaria infection. These results show the benefit of taking a detailed, protein-level approach to understanding the innate immune response of aquatic invertebrates to macroparasite infection.

Tetraploid induction of Crassostrea hongkongensis and C. sikamea by inhibiting the polar body 1 release in diploid fertilized eggs - Yanping Qin; Zohaib Noor; Xingyou Li; Haitao Ma; Jun Li; Yinyin Zhou; Riguan Mo; Yuehuan Zhang; Ziniu Yu (Marine Life Science & Technology, 2021)

In-situ Detection Method for Microplastics in Water by Polarized Light Scattering - Tong Liu; Shijun Yu; Xiaoshan Zhu; Ran Liao; Zepeng Zhuo; Yanping He; Hui Ma (Frontiers in Marine Science, 2021)
Microplastics (MPs) have become the widespread contaminants, which raises concerns on their ecological hazards. In-situ detection of MP in water bodies is essential for clear assessment of the ecological risks of MPs. The present study proposes a method based on polarized light scattering which measures the polarization parameters of the scattered light at 120° to detect MP in water. This method takes the advantage of in-situ measurement of the individual particles and the experimental setup in principle is used. By use of the measured polarization parameters equipped by machine learning, the standard polystyrene (PS) spheres, natural water sample, and lab-cultured microalgae are explicitly discriminated, and MP with different physical and chemical properties can be differentiated. It can also characterize the weathering of different MP and identify the specific type from multiple types of MP. This study explores the capability of the proposed method to detect the physical and chemical properties, weathering state and concentration of MP in water which promises the future application in water quality sensing and monitoring.

Plant multiscale networks: charting plant connectivity by multi-level analysis and imaging techniques - Xi Zhang; Yi Man; Xiaohong Zhuang; Jinbo Shen; Yi Zhang; Yaning Cui; Meng Yu; Jingjing Xing; Guangchao Wang; Na Lian; Zijian Hu; Lingyu Ma; et al. (Science China Life Sciences, 2021)

A Significant Genetic Admixture in Farmed Populations of the Noble Scallop Chlamys nobilis Revealed by Microsatellite DNA Analysis in Southern China - Haitao Ma; Dongmei Yu; Shu Xiao; Yanping Qin; Yang Zhang; Jun Li; Yuehuan Zhang; Ziniu Yu (Frontiers in Marine Science, 2021)
The noble scallop, Chlamys nobilis , is an important bivalve mollusk with high commercial value and is usually farmed in the waters of southern China. To date, very little is known about the genetic diversity and population structure of C. nobilis . In this study, 10 microsatellite loci of four farmed C. nobilis populations were compared with one another and compared wild population in southern China. A total of 83 alleles were found. Surprisingly, the level of genetic diversity of the farmed C. nobilis populations was higher than that of the wild population. Although the population genetic of wild population was completely in the Hardy–Weinberg equilibrium, due to heterozygote deficiency, significant deviations from the Hardy–Weinberg equilibrium were found in all farmed populations, suggesting a genetic admixture caused by the mixing of seeds from various hatcheries. The Fst and AMOVA values showed significant genetic differences between wild and farmed populations. The Bayesian assignment also confirmed that genetic admixture was significant and widespread in artificial breeding of C. nobilis . Furthermore, the UPGMA tree topology and PCA demonstrated that the genetic diversity of wild population can be clearly distinguished from farmed populations. In a nutshell, the findings of this study not only fill the knowledge gaps in genetic diversity of wild and farmed C. nobilis populations, but also serve as a guide for maintaining the genetic diversity of C. nobilis in both farmed and wild populations.

Genetic Recombination of the Mantle Color Pattern of Two Boring Giant Clam (Tridacna crocea) Strains - Junjie Wang; Zihua Zhou; Haitao Ma; Jun Li; Yanping Qin; Jinkuan Wei; Xingyou Li; Qingliang Liao; Yunqing Li; Gongpengyang Shi; Yinyin Zhou; Yuehuan Zhang; et al. (Frontiers in Marine Science, 2021)
According to the RGB law display, the polymorphism of the giant clam mantle color pattern is through four iridocytes. The boring giant clam ( Tridacna crocea ) exhibits diverse mantle colors, including blue, green, purple, gold, and orange. In order to evaluate the genetic laws driving these mantle color patterns, a complete diallel cross between two color strains [blue strain (only blue iridocyte) and the yellow-green strain (yellow and green iridocytes)] was performed. Using a single-to-single mating system, two intra-strain crosses (BB and YY) and two reciprocal inter-strain crosses (BY and YB) were produced in triplicates. Higher fertilization rate and hatching rate were observed in all experimental groups, suggesting that there was no sperm–egg recognition barrier between the two strains. In the grow-out stage, the size of the reciprocal hybrids was larger than that of the two pure strains with a degree of heterosis. In addition, compared with the two pure strains, the hybrids have higher larval metamorphosis rate and higher survival rate. At 1 year of age, the mantle color pattern of pure strains showed 100% stable inheritance, while the reciprocal hybrids exhibited colorful patterns (a combination of blue, yellow, and green), suggesting that there was a genetic recombination of the mantle colors during the stable expression period. These results provide a theoretical basis for the formation of the mantle color of giant clam and its genetic segregation law, as well as provide guidance for genetic breeding of giant clams.

LncRNA TRHDE-AS1 inhibit the scar fibroblasts proliferation via miR-181a-5p/PTEN axis - Yanping Wei; Tingting Wang; Ningning Zhang; Yunyun Ma; Siji Shi; Ruxing Zhang; Xianzhao Zheng; Lindong Zhao (Journal of Molecular Histology, 2021)
Hypertrophic scar (HS), a fibroproliferative disorder caused by abnormal wound healing after skin injury, which is characterized by excessive deposition of extracellular matrix and invasive growth of fibroblasts. Recent studies have shown that some non-coding RNA implicated the formation of HS, but the mechanism remains unclear. In this study, we found that lncRNA TRHDE-AS1 was downregulated in HS tissues and HSFs, and the level of lncRNA TRHDE-AS1 negatively correlated with the level of miR-181a-5p in HS tissue and HSFs. Overexpressed lncRNA TRHDE-AS1 significantly suppressed miR-181a-5p level, while promoted HSFs apoptosis and inhibited HSFs proliferation. Further study shown that PTEN was a direct target of miR-181a-5p, and lncRNA TRHDE-AS1 served as a molecular sponge for miR-181a-5p to regulate the expression of PTEN. Overexpression of PTEN could eliminate lncRNA TRHDE-AS1-mediated proliferation suppression of HSFs. In conclusion, our study suggested that lncRNA TRHDE-AS1/miR-181a-5p/PTEN axis plays an important role in promoting hypertrophic scar formation, which may be effectively used as a therapeutic target for hypertrophic scar treatment.

Characterization of a novel brain cell line from Jian carp (Cyprinus carpio var. Jian) - Ying Li; Yanping Ma; Le Hao; Jiangyao Ma; Zhiling Liang; Zhenxing Liu; Hao Ke; Yugu Li (Fish Physiology and Biochemistry, 2021)

Effects of Symbiodiniaceae Phylotypes in Clades A–E on Progeny Performance of Two Giant Clams (Tridacna squamosa and T. crocea) During Early History Life Stages in the South China Sea - Chao Long; Yuehuan Zhang; Yunqing Li; Jun Li; Zihua Zhou; Yanping Qin; Xingyou Li; Haitao Ma; Jinkuan Wei; Yinyin Zhou; Zohaib Noor; Lijuan Long; et al. (Frontiers in Marine Science, 2021)
Unlike most bivalves, giant clams (tridacnids) harbor symbiotic microalgae (zooxanthellae) in their other fleshy bodies. The effects of mixed populations of zooxanthellae on larval metamorphosis has been reported in several papers, but there have been very few studies on the effects of single zooxanthella species on the establishment of symbiosis in giant clams. In this study, we obtained five pure zooxanthella species (clades A3, B1, C1, D1, E1) from antler coral by molecular identification, and analyzed their effects on the larval metamorphosis and progeny performance of two giant clams, Tridacna squamosa and T. crocea , in the South China Sea. Clam larvae with all five zooxanthella species underwent larval settlement and metamorphosis, and formed the zooxanthellal tubular system. There was some variation in metamorphic rate and time to metamorphosis between clams with different zooxanthella species, but no significant differences in size at metamorphosis. After metamorphosis, larvae with all zooxanthella types continued to develop normally. Mantle color was consistent within clam species and zooxanthella species had no effect on mantle color. However, clam progeny with clade E1 zooxanthellae were smaller than progeny with the other four zooxanthella clades (A3, B1, C1, and D1). Survival rate was over 90% for all progeny and there were no significant differences in survival between progeny with Symbiodinium clades A–E during the entire culture process. Two-way ANOVA analysis revealed that giant clam species was the main factor influencing progeny growth, with some variation in growth attributable to zooxanthella type. Our results provide new information on both the symbiotic relationship between giant clams and zooxanthellae and the mantle coloration of giant clams, and will be useful in giant clam seed production and aquaculture.

Associations of Serum Selenium Levels in the First Trimester of Pregnancy with the Risk of Gestational Diabetes Mellitus and Preterm Birth: a Preliminary Cohort Study - Peng Ju Liu; Aimin Yao; Liangkun Ma; Xiao Yan Chen; Song Lin Yu; Yanping Liu; Yi Xuan Hou (Biological Trace Element Research, 2021)

Associations of TMPRSS6 Polymorphisms with Gestational Diabetes Mellitus in Chinese Han Pregnant Women: a Preliminary Cohort Study - Peng Ju Liu; Aimin Yao; Xiao Yan Chen; Yanping Liu; Liangkun Ma; Yi Xuan Hou (Biological Trace Element Research, 2021)

Pseudorabies virus encephalitis in humans: a case series study - Siyuan Fan; Hongxun Yuan; Lei Liu; Hongfang Li; Shengnan Wang; Weili Zhao; Yihan Wu; Pei Wang; Yafang Hu; Jun Han; Yanli Lyu; Wuchao Zhang; et al. (Journal of NeuroVirology, 2020)

Levels of human cytomegalovirus miR-US25-1-5p and miR-UL112-3p in serum extracellular vesicles from infants with HCMV active infection are significantly correlated with liver damage - Jing Zhang; Yujing Huang; Qing Wang; Yanping Ma; Ying Qi; Zhongyang Liu; Jingui Deng; Qiang Ruan (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Three-dimensional reconstruction of Picea wilsonii Mast. pollen grains using automated electron microscopy - Weiwei Shen; Lingyu Ma; Xi Zhang; Xixia Li; Yuanyuan Zhao; Yanping Jing; Yun Feng; Xueke Tan; Fei Sun; Jinxing Lin (Science China Life Sciences, 2020)

Digestive enzyme activity of the Japanese grenadier anchovy Coilia nasus during spawning migration: influence of the migration distance and the water temperature - Fengjiao Ma; Yanping Yang; Min Jiang; Denghua Yin; Kai Liu (Journal of Fish Biology, 2019)
In this study, we investigated the activity levels of two major digestive enzymes (pepsin and lipase) in the commercially important Japanese grenadier anchovy Coilia nasus during its upstream migration to analyse the digestive physiological responses to starvation and to analyse the influence of the water temperature on enzyme activity. Water temperature had a significant effect on pepsin activity, while long‐term starvation resulted in a significant decrease in pepsin activity. As starvation continued, however, a slight increase in pepsin activity between the Wuhu (440 river km) and Anqing (620 river km) regions may indicate that C. nasus had refeeding behaviour due to its large expenditure of energy reserves. In contrast, lipase activity was not significantly affected by the water temperature but the effect of fasting increased as much as 13% of lipase activity from the Chongming region (20 river km) to Anqing region, suggesting that the stored lipids of grenadier anchovy were mobilised to meet energy requirements of upstream migration activity and gonad development. Lipid mobilisation activated lipoprotein lipase (LPL; proteins with lipase activity) to hydrolyse triacylglycerides (TAG), which is the first step of lipid assimilation and obtained energy from fatty acids under fasting conditions. Therefore, the increased lipase activity is attributed mainly to the lipase that is involved in endogenous lipid hydrolysis. Grenadier anchovy appears to adapt to long‐term starvation during migration and the increased lipase activity may indicate a crucial effect on lipid metabolism. This study demonstrated that distinct alterations occur in pepsin and lipase activities during the spawning migration of grenadier anchovy due to exogenous nutrition and endogenous metabolism. Furthermore, it provides a basis for further research on the digestive physiology and energy metabolism in this species.

Anti-proliferation effects of ethanolic extracts from Sophora moorcroftiana seeds on human hepatocarcinoma HepG2 cell line - Gang Su; Wenke Yang; Wenbo Meng; Qionghui Wu; Yanping Luo; Xingming Ma; Shen Zhao; Xiaodong Xie; Guang-Qin Guo (Natural Product Research, 2018)

Recent land cover changes and sensitivity of the model simulations to various land cover datasets for China - Liang Chen; Zhuguo Ma; Rezaul Mahmood; Tianbao Zhao; Zhenhua Li; Yanping Li (Meteorology and Atmospheric Physics, 2017)

Human cytomegalovirus-encoded miR-US4-1 promotes cell apoptosis and benefits discharge of infectious virus particles by targeting QARS - Yaozhong Shao; Ying Qi; Yujing Huang; Zhongyang Liu; Yanping Ma; Xin Guo; Shujuan Jiang; Zhengrong Sun; Qiang Ruan (Journal of Biosciences, 2016)

A cluster of 3′ coterminal transcripts from US12–US17 locus of human cytomegalovirus - Ying Lu; Yanping Ma; Zhongyang Liu; Liying Han; Shuang Gao; Bo Zheng; Chang Liu; Ying Qi; Zhengrong Sun; Yujing Huang; Qiang Ruan (Virus Genes, 2016)

Applications of Savitzky-Golay Filter for Seismic Random Noise Reduction - Yanping Liu; Bo Dang; Yue Li; Hongbo Lin; Haitao Ma (Acta Geophysica, 2016)

Pharmacodynamics and Pharmacokinetics of Levobupivacaine Used for Epidural Anesthesia in Patients with Liver Dysfunction - Juhong Ran; Yanping Wang; Fangkun Li; Wei Zhang; Minyu Ma (Cell Biochemistry and Biophysics, 2015)

Genomic organization of a novel victorivirus from the rice blast fungus Magnaporthe oryzae - Lihua Tang; Yanping Hu; Lijiang Liu; Songsong Wu; Jiatao Xie; Jiasen Cheng; Yanping Fu; Guoming Zhang; Juntao Ma; Yongli Wang; Liyan Zhang (Archives of Virology, 2015)

Human cytomegalovirus miR-UL36-5p inhibits apoptosis via downregulation of adenine nucleotide translocator 3 in cultured cells - Xin Guo; Yujing Huang; Ying Qi; Zhongyang Liu; Yanping Ma; Yaozhong Shao; Shujuan Jiang; Zhengrong Sun; Qiang Ruan (Archives of Virology, 2015)

Effects of hydrogen peroxide accumulation, lipid peroxidation, and polyphenol oxidation during superficial scald development in ‘Fuji’ apples - Xingang Lu; Yanping Ma; Xinghua Liu (Horticulture, Environment, and Biotechnology, 2014)

Down-regulation of human cytomegalovirus UL138, a novel latency-associated determinant, by hcmv-miR-UL36 - Yujing Huang; Ying Qi; Yanping Ma; Rong He; Yaohua Ji; Zhengrong Sun; Qiang Ruan (Journal of Biosciences, 2013)

Overlapping transcription structure of human cytomegalovirus UL140 and UL141 genes - Yanping Ma; Mali Li; Bo Zheng; Ning Wang; Shuang Gao; Lin Wang; Ying Qi; Zhengrong Sun; Qiang Ruan (Journal of Biosciences, 2013)

Transcription characteristics of the human cytomegalovirus UL13 gene - Ning Wang; Yanping Ma; Mali Li; Shuang Gao; Lin Wang; Ying Qi; Yaohua Ji; Zhengrong Sun; Qiang Ruan (Archives of Virology, 2013)

Cloning and expression of genes related to the sucrose-metabolizing enzymes and carbohydrate changes in peach - Chunhua Zhang; Zhijun Shen; Yanping Zhang; Jian Han; Ruijuan Ma; Nicholas Kibet Korir; Mingliang Yu (Acta Physiologiae Plantarum, 2013)

Computational identification of microRNAs in peach expressed sequence tags and validation of their precise sequences by miR-RACE - Yanping Zhang; Mingliang Yu; Huaping Yu; Jian Han; Changnian Song; Ruijuan Ma; Jinggui Fang (Molecular Biology Reports, 2012)

Human cytomegalovirus RL13 gene transcripts in a clinical strain - Mali Li; Yanping Ma; Yaohua Ji; Rong He; Ying Qi; Zhengrong Sun; Ning Wang; Shuang Gao; Qiang Ruan (Virus Genes, 2011)

Transcription pattern of UL131A-128 mRNA in clinical strains of human cytomegalovirus - Zhengrong Sun; Gaowei Ren; Yanping Ma; Ning Wang; Yaohua Ji; Ying Qi; Mali Li; Rong He; Qiang Ruan (Journal of Biosciences, 2010)

Diagnostic value of HCMV pp65 antigen detection by FCA for symptomatic and asymptomatic infection: compared to quantification of HCMV DNA and detection of IgM antibody in infants - Zhengrong Sun; Xiangshi Ceng; Zhiqin Mao; Jidong Wang; Qing Liu; Yaohua Ji; Yanping Ma; Ying Qi; Rong He; Qiang Ruan (Medical Microbiology and Immunology, 2009)

Human cytomegalovirus UL145 gene is highly conserved among clinical strains - Zhengrong Sun; Ying Lu; Qiang Ruan; Yaohua Ji; Rong He; Ying Qi; Yanping Ma; Yujing Huang (Journal of Biosciences, 2007)